Export Consortia in Developing Countries Successful Management of Cooperation Among SMEs - Antoldi, Fabio (Springer Berlin Heidelberg, 2011)
This volume presents an analysis of export consortia from a strategic management perspective. It builds on the empirical study of nine export consortia promoted by UNIDO in developing countries between 2004 and 2007. Drawing heavily on the experience of actual export consortia, the book combines a rigorous research approach with a more pragmatic view of the phenomenon. Although aimed primarily at academics in the field of management, the material will be of interest to a variety of readers. A comprehensive literature review combines the topics of SME internationalization, strategic networks, and those issues which relate specifically to SME alliances in the form of export consortia. For entrepreneurs and executives, a number of business models and management tools for the successful design and implementation of export consortia are included. Insights into the functioning of export consortia will also be of interest to policy-makers and institutions involved in the development of support programs for the growth of SMEs in developing countries.